Molar Tooth Sign with Deranged Liver Function Tests: An Indian Case with COACH Syndrome - Rama Krishna Sanjeev; Seema Kapoor; Manisha Goyal; Rajiv Kapur; Joseph Gerard Gleeson (Case Reports in Pediatrics)
We report the first genetically proven case of COACH syndrome from the Indian subcontinent in a 6-year-old girl who presented with typical features of Joubert syndrome along with hepatic involvement. Mutation analysis revealed compound heterozygous missense mutation in the known gene TMEM67 (also called MKS3).